ANALYSIS OF AUDIT QUALITY BEFORE AND DURING PANDEMIC AT FOOD & BAVERAGES COMPANY - Kusumah, R. Wedi Rusmawan; Adriani, Helmi P.; Safitri, Kirana A.; Agustin, Dhika P.; Oktavia, Resy; Wendari, S. Ayulia; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study focuses on audit quality in assessing audit type, financial performance, company size, and gearing ratio in companies Food and Baverages before and during the pandemic. The purpose of this study is to evaluate the role of audit quality as the basis for analyzing audit quality in assessing the type of audit, financial performance, company size, and the current gearing ratio of a company. The method used is a quantitative research method where this study proves the variables with certain theories and uses the Multiple Regression Analysis method with a sample of 25 company data. The data collection method is done by collecting data on companies Food and Baverages listed on the Indonesia Stock Exchange. This data analysis method compares. The results of this study indicate that all variables in this study do not have a positive effect on audit quality.